2013
DOI: 10.3109/10717544.2013.838718
|View full text |Cite
|
Sign up to set email alerts
|

A novel subcutaneous infusion delivery system based on osmotic pump:in vitroandin vivoevaluation

Abstract: School of Pharmacy, Zhejiang University, Hangzhou, P.R. China AbstractAn economical, convenient portable drug delivery system combining osmotic pump with subcutaneous infusion was developed, which was composed of three primary components: water chamber, osmotic pump chamber and support base. Ceftriaxone sodium (CRO) was selected as the model drug and osmotic pump tablets were prepared. The influence of osmotic agents on drug release profiles was evaluated. As the adjustment made by the osmotic agents was limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 32 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…With the advent of CRISPR/CAS genome editing, HTS, and the optimized drug discovery work flow, the demand for effective, scalable, quick to set up gene delivery methods is an expanding need. Research studies into developing novel nonviral gene delivery agents continue to grow and have provided important data on their feasibility and applicability [ 26 , 27 ]. This is illustrated by the recent investigation of at least 7 different nonviral delivery systems in various phases of clinical study [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of CRISPR/CAS genome editing, HTS, and the optimized drug discovery work flow, the demand for effective, scalable, quick to set up gene delivery methods is an expanding need. Research studies into developing novel nonviral gene delivery agents continue to grow and have provided important data on their feasibility and applicability [ 26 , 27 ]. This is illustrated by the recent investigation of at least 7 different nonviral delivery systems in various phases of clinical study [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gong et al also developed an osmotic micropump with an additional water chamber that enabled the release process to be actuated without extra release medium. 316 With this device, the subcutaneous administration of ceftriaxone sodium was realized, exhibiting constant blood concentration with minimized fluctuations in contrast to intravenous injection.…”
Section: Microfluidic Micropumps For Drug Deliverymentioning
confidence: 99%
“…The saturated salt solution was diluted and amplified by the water chamber through the linking hollow fiber, after which the diluted solution entered the extrusion chamber, leading to the release of the liquid in the compressible reservoir. Gong et al also developed an osmotic micropump with an additional water chamber that enabled the release process to be actuated without extra release medium . With this device, the subcutaneous administration of ceftriaxone sodium was realized, exhibiting constant blood concentration with minimized fluctuations in contrast to intravenous injection.…”
Section: Microfluidics For Drug Delivery and Drug Carrier Fabricationmentioning
confidence: 99%
“…Comprehensive grading method was employed to evaluate the release profiles of various formulations compared with the ideal release profiles. The score of various formulations was calculated by the following equation (Gong et al, 2014):…”
Section: Optimization Of the Formulationmentioning
confidence: 99%
“…There are some successful reports about the development of drug delivery systems by utilizing osmosis (Theeuwes & Yum, 1976;Lee & Cima, 2011). Previously, our research team has reported an osmotic tablet pump for subcutaneous infusion (Gong et al, 2014). However, this infusion system was difficult to maintain its sterility during the preparation process, and the drug content cannot be altered once manufacturing is completed.…”
Section: Introductionmentioning
confidence: 99%